Reversible Modulation of 2D Photonic Crystals with a Responsive Shape‐Memory DNA Hydrogel Film. Issue 18 (26th July 2019) - Wang, Chunyan; Li, Fengyun; Bi, Yanhui; Guo, Weiwei
Abstract: Responsive DNA hydrogels are smart soft materials that have attracted significant attention in the past decade in various research fields, especially in biosensing. However, several limitations of DNA hydrogels, such as non‐recyclability, slow response, and high manufacturing cost, severely hamper their biosensing applications. In this work, shape‐memory DNA hydrogel film with thickness at micrometer scale is developed, serving as both target recognition unit and actuating unit for the regulation of 2D photonic crystals (2D PCs) embedded on the surface of the hydrogel film. External stimuli can drive the reversible shape changes of the DNA hydrogel films and therefore modulate the lattice spacing of 2D PC array, which can be directly observed by the diameter changes of the Debye diffraction ring. Compared with the bulk hydrogels, these DNA hydrogel films possess the advantages of lower cost and faster stimuli response; more importantly, diameter of the diffraction ring as signal output avoids the requirement of sophisticated instruments. pH‐responsive or Ag + /cysteine (Cys) responsive DNA hydrogel films are successfully developed as model systems to demonstrate the successful reversible modulation of the lattice spacing of 2D PCs. These smart DNA hydrogel film systems may have great potential in the development of future portable and visual biosensing devices. Abstract : Target‐responsive shape‐memory DNA hydrogel films serving as actuating unit for regulation of 2D photonic crystals (2D PCs) are developed. pH‐ and Ag + /Cys responsive 2D PC‐DNA hydrogel films, as model systems, are constructed and applied in the sensing of specific analyte, with the advantages of reduced DNA usage, fast response and simple signal output compared with bulk hydrogel‐based sensors.